Evidence of strong stabilizing effects on the evolution of boreoeutherian (Mammalia) dental proportions. Issue 13 (14th June 2019) - Monson, Tesla A.; Boisserie, Jean‐Renaud; Brasil, Marianne F.; Clay, Selene M.; Dvoretzky, Rena; Ravindramurthy, Shruti; Schmitt, Christopher A.; Souron, Antoine; Takenaka, Risa; Ungar, Peter S.; Yoo, Sunwoo; Zhou, Michael; et al.
Abstract: The dentition is an extremely important organ in mammals with variation in timing and sequence of eruption, crown morphology, and tooth size enabling a range of behavioral, dietary, and functional adaptations across the class. Within this suite of variable mammalian dental phenotypes, relative sizes of teeth reflect variation in the underlying genetic and developmental mechanisms. Two ratios of postcanine tooth lengths capture the relative size of premolars to molars (premolar–molar module, PMM), and among the three molars (molar module component, MMC), and are known to be heritable, independent of body size, and to vary significantly across primates. Here, we explore how these dental traits vary across mammals more broadly, focusing on terrestrial taxa in the clade of Boreoeutheria (Euarchontoglires and Laurasiatheria). We measured the postcanine teeth of N  = 1, 523 boreoeutherian mammals spanning six orders, 14 families, 36 genera, and 49 species to test hypotheses about associations between dental proportions and phylogenetic relatedness, diet, and life history in mammals. Boreoeutherian postcanine dental proportions sampled in this study carry conserved phylogenetic signal and are not associated with variation in diet. The incorporation of paleontological data provides further evidence that dental proportions may be slower to change than is dietary specialization. These results have implications for our understanding of dental variation and dietary adaptation in mammals. Abstract : Relative sizes of mammalian teeth, particularly as captured by the premolar–molar module (PMM) and the molar module component (MMC), reflect variation in underlying genetic and developmental mechanisms. We measured the postcanine teeth of N  = 1, 523 terrestrial boreoeutherians to test hypotheses about associations between dental proportions and phylogenetic relatedness, diet, and life history in mammals. Our study finds evidence of strong stabilizing effects on postcanine dental proportions, associated with conserved phylogenetic signal and independent of variation in diet, a result with evolutionary implications for our understanding of dental variation and dietary adaptation in mammals.